MAIN DIRECTIONS OF MODERN GEOMORPHOLOGICAL RESEARCH BY GEOGRAPHERS OF THE WESTERN REGION IN THE 19TH–20TH CENTURIES - Потапова, Алла (SWorldJournal, 2025)
The study is devoted to a comprehensive geographical analysis of the concept of «geomorphology» and the main directions of its development in the western region during the 19th–20th centuries. It examines the formation and evolution of scientific schools